Cover Feature: On‐Surface Synthesis and Characterization of Acene‐Based Nanoribbons Incorporating Four‐Membered Rings (Chem. Eur. J. 52/2019). Issue 52 (25th July 2019) - Sánchez‐Sánchez, Carlos; Dienel, Thomas; Nicolaï, Adrien; Kharche, Neerav; Liang, Liangbo; Daniels, Colin; Meunier, Vincent; Liu, Junzhi; Feng, Xinliang; Müllen, Klaus; Sánchez‐Valencia, Juan Ramón; Gröning, Oliver; et al.
Abstract : Making nanoribbons from acenes : Tetracene‐based nanoribbons comprising cyclobutadiene moeities have been rationally synthesized from ortho‐tetrahalogenated tetracene precursors on a metallic surface following a bottom‐up approach. The structural, electronic, and magnetic properties of these and other related nanostructures have been characterized following a multitechnique approach including scanning probe microscopies and theoretical calculations. More information can be found in the Full Paper by C. Sánchez‐Sánchez, R. Fasel, et al. on page 12074 .